DDM: Delay driven layer assignment algorithm based on deployment mechanism - Bao, Chenpeng; Xu, Saijuan; Chen, Zhen (IEEE International Conference on Consumer Electronics-China (Online), 2021)
This paper proposes a delay driven layer assignment algorithm which selects the routing layer by setting a wire segment deployment mechanism. The proposed algorithm mainly includes an improved segment weighting strategy and a via constraint strategy. The proposed algorithm could reduce via count while optimizing delay, and provide a better global routing result for guiding the following detail routing.